Verification and validation as definition of quality in the software testing - Zarharova, O. I. (My University, 2020)
Quality of software defines by several metrics described by standards, like ISO/IEC 9126 (external and internal quality, quality in use). Software testing helps us to measure the quality of software in terms of the number of defects found, the tests run, and the system covered by the tests.Verification and validation processes are presented through all software testing process.
Keywords: Verification; Validation